2019
DOI: 10.1080/21691401.2019.1610415
|View full text |Cite|
|
Sign up to set email alerts
|

6-Gingerol protects cardiocytes H9c2 against hypoxia-induced injury by suppressing BNIP3 expression

Abstract: Background: Cardiomyocytes loss is the predominant pathogenic characteristic in the hypoxia-induced injury. Meanwhile, it has been corroborated that Bcl-2 E1B 19-KDa interacting protein 3 (BNIP3) provokes apoptosis and autophagy. For moderating cardiomyocytes loss, we initially probed the cyto-protection effects of 6-Gingerol (6 G), meanwhile, its potential mechanisms associated with BNIP3 were elucidated in our studies. Methods: We pretreated cardiomyocytes H9c2 cells with 6 G at different concentrations (0-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…Flow cytometry analysis was applied by assessing the apoptotic cell death 25 . Apoptosis rates were estimated via Annexin V–FITC/PI apoptosis kit (BD biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…Flow cytometry analysis was applied by assessing the apoptotic cell death 25 . Apoptosis rates were estimated via Annexin V–FITC/PI apoptosis kit (BD biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…102 In another study, 6G induced the expression of PI3K/AKT/mTOR, thus reducing cardiomyocyte apoptosis and autophagy. 117,120 Given the anti-inflammatory and antioxidative properties of 6G, further investigations of 6G in CVD, including diabetes and insulin resistance and atherosclerotic and cardiometabolic disease, are warranted. nanomedicines has been implicated as promising drug delivery system methods in a variety of CVD, mainly due to the capacity of the nanomedicines to be mobilized in the vascular system and other organelles for multiple purposes.…”
Section: -Gingerolmentioning
confidence: 99%
“…Therefore, there is an urgent need to explore new treatments. Recent studies have shown that 6-Gingerol, as a new Chinese herbal medicine in nervous system therapy, has significant therapeutic anti-inflammatory, anti-apoptotic and anti-oxidative stress effects ( Ren et al, 2019 ; Sun et al, 2020 ; Zahoor et al, 2020 ). In present study, we explored the therapeutic effect of 6-Gingerol in HIBI model, defined its benefical effects in acute and long-term injury.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that 6-Gingerol can reduce neuroinflammatory responses in primary peripheral nerve injury in mice and play an anti-inflammatory role in mastitis and myocardial fibrosis ( Borgonetti et al, 2020 ; Han et al, 2020 ; Zahoor et al, 2020 ). In hypoxia-induced cardiomyocyte injury, 6-Gingerol can enhance the vitality of cardiomyocytes, and reduce apoptosis and oxidant stress, thereby protecting cardiomyocytes from hypoxic damage ( Ren et al, 2019 ). The above studies have fully suggested that 6-Gingerol can play a protective role in hypoxia induced cell injury and neuroinflammation response.…”
Section: Discussionmentioning
confidence: 99%